2016
DOI: 10.1038/srep34466
|View full text |Cite
|
Sign up to set email alerts
|

Activation and increase of radio-sensitive CD11b+ recruited Kupffer cells/macrophages in diet-induced steatohepatitis in FGF5 deficient mice

Abstract: We have recently reported that Kupffer cells consist of two subsets, radio-resistant resident CD68+ Kupffer cells and radio-sensitive recruited CD11b+ Kupffer cells/macrophages (Mφs). Non-alcoholic steatohepatitis (NASH) is characterized not only by hepatic steatosis but also chronic inflammation and fibrosis. In the present study, we investigated the immunological mechanism of diet-induced steatohepatitis in fibroblast growth factor 5 (FGF5) deficient mice. After consumption of a high fat diet (HFD) for 8 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 47 publications
3
40
0
Order By: Relevance
“…In human NASH samples, CYP7B1 expression is increased and this is believed to be an attempt by the liver to reduce hepatotoxicity during disease progression to NASH 47 . Other negatively affected genes include Adgre1 48 , Cd5l 49 , and Cd68 50 , all which are associated with NAFLD pathology. In fact, Cd68 is a typical monocyte/macrophage marker 51 , which could suggest that TAT-Gap19 has an effect on the recruitment of monocytes to the liver 52 .…”
Section: Discussionmentioning
confidence: 99%
“…In human NASH samples, CYP7B1 expression is increased and this is believed to be an attempt by the liver to reduce hepatotoxicity during disease progression to NASH 47 . Other negatively affected genes include Adgre1 48 , Cd5l 49 , and Cd68 50 , all which are associated with NAFLD pathology. In fact, Cd68 is a typical monocyte/macrophage marker 51 , which could suggest that TAT-Gap19 has an effect on the recruitment of monocytes to the liver 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Klein et al [21] demonstrated that tissue-resident (sessile) Kupffer cells are radioresistant while monocyte-derived macrophages are radiosensitive. The CD68 + subset is also radioresistant but the CD11b + subset is radiosensitive [25] . The authors of the present study and many other investigators believe that tissueresident Kupffer cells are involved in the clearance of microorganisms while the monocyte-derived macrophages are involved in the induction of inflammation and play a role in immune surveillance [22] .…”
Section: Discussionmentioning
confidence: 99%
“…The CD11b + mMØs were also found to accumulate in the liver following repeated lipopolysaccharide injections, but suppressed TNF efflux into the systemic circulation, thereby reducing lethal septicemia ( 60 ). In addition, the CD11b + mMØs were recruited during diet-induced steatohepatitis in FGF5 deficient mice and following partial hepatectomy, where they were crucial for liver regeneration ( 61 , 62 ). Others have observed that monocyte derived cells protect the liver from iron toxicity in hemolytic anemia by ingesting senescent and dying erythrocytes ( 63 ).…”
Section: Introduction To Macrophages In the Livermentioning
confidence: 99%